Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1308/rcsbull.2020.132
|View full text |Cite
|
Sign up to set email alerts
|

Altmetrics and citations: the impact of journal publications

Abstract: How researchers can benefit from alternative measures to make their mark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Belter 35 suggested that 2 years post publication are needed to allow for reliable bibliometric indicators, with some suggestions that 3 years post-publication data are preferable. 25 Citations and altmetrics provide different aspects of impact, and there has been considerable debate about the degree with which they correlate, with Noah et al 36 suggesting that both aspects of metrics are important, but that neither gives the whole picture in terms of impact. It is likely for both that their value depends on factors other than quality and originality, including the age of the references, journal impact factor and funding agencies.…”
Section: Limitationsmentioning
confidence: 99%
“…Belter 35 suggested that 2 years post publication are needed to allow for reliable bibliometric indicators, with some suggestions that 3 years post-publication data are preferable. 25 Citations and altmetrics provide different aspects of impact, and there has been considerable debate about the degree with which they correlate, with Noah et al 36 suggesting that both aspects of metrics are important, but that neither gives the whole picture in terms of impact. It is likely for both that their value depends on factors other than quality and originality, including the age of the references, journal impact factor and funding agencies.…”
Section: Limitationsmentioning
confidence: 99%
“…Accordingly, articles with simple, sensationalist, and declarative titles receive higher AAS, irrespective of their scientific impact. 45,46 The evidence level is also considered a pivotal quality indicator of scientific work. 16 However, most of the top 101 AAS articles were retrospective studies, which has been reported in other altmetric papers such as total joint arthroplasty before.…”
Section: Aas and Bibliometricsmentioning
confidence: 99%
“…Nowadays, many routes outside PubMed are used by authors to track and share new publications in their field; for example, Google scholar or social media are increasingly used. Although there are conflicting reports on whether social media attention can enhance citation rates (some studies report a weak positive correlation, e.g., Costas et al, 2014, Barakat et al, 2018, whereas others found no correlation, e.g., Noah et al, 2020), there is evidence that articles which receive high views/downloads soon after publication are candidates for strong citation (Bommann & Haunschild, 2018). In recognition of the plurality of routes by which readers identify articles of interest and the importance of visibility upon publication, we plan to expand activities to promote journal content in the first months after As examples, we will increase the frequency of topical Calls for Papers and (in addition to promoting single papers in social media or by press release) will make more systematic use of collections of related papers, as they are built up on publication, through a Call or by matched keywords.…”
Section: E D I T O R I a L Physiological Reports: Standing Openly For...mentioning
confidence: 99%